Análise bacteriológica da água utilizada nos equipos odontológicos do serviço público de Aracaju/SE - Paixão, Mônica Silveira (2006)
Through bacteriological analyses, quality of water used in odontologic equipment of the Public Service in Aracaju was evaluated. 118 water samples were collected from 59 equipments and distributed in three groups according to the localization of the reservoirs and the system availability of Flush Antisepsis. The present research was supposed to investigate the contamination with total and fecal coliforms in the water used in 24 equipments of Odontology Department and 35 equipments of Health Basic Units, which corresponds to 50% of total odontologic equipment in functioning in the Federal and Municipal Public Service. Also, the relation between quality of water and mark of Odontologic Equipment/Time of working of the same ones was analyzed. The samples were analyzed in Applied Microbiology Laboratory in the Federal University of Sergipe, from April 2005 to March 2006, using the Multiple Pipes Technique. Among 118 analyzed samples, 03 (three) them were unsuitable for human consumption and, consequently, for odontologic use, according to the current law in Brazil. The bactericidal effects of the Flush system were not observed, independent of the mark and time of the equipment functioning.